(untitled) (Journal of actual problems of jurisprudence, 2018)
Cyber terrorism conjures up images of vicious terrorists unleashing catastrophic at-tacks against computer networks, wreaking havoc, and paralyzing nations. This is a frightening scenario, but how likely is it to occur? Could terrorists cripple critical military, financial, and service computer systems? Psychological, political, and economic forces have combined to promote the fear of cyber terrorism. From a psychological perspective, two of the greatest fears of modern time are combined in the term «cyber terrorism.» The fear of random, violent victimization segues well with the distrust and outright fear of computer technology. Many of these fears, the report contends, are exaggerated: not a single case of cyber terrorism has yet been recorded, hackers are regularly mistaken for terrorists, and cyber defenses are more robust than is commonly supposed. Even so, the potential threat is undeniable and seems likely to increase, making it all the more important to address the danger without inflating or manipulating it. Key words: Cyber terrorism, computer, communication, information.